2012
DOI: 10.1504/ijssca.2012.053472
|View full text |Cite
|
Sign up to set email alerts
|

Six Sigma implementation to minimise weight variation for Baby Lido Diaper manufacturing company

Abstract: The increasing demand in baby diaper products in addition to customer requirements has compelled companies to improve the quality of their production processes. This paper presents a customised Six Sigma procedure to reduce weight variation in diaper products. To this end, a define, measure, analyse, improve and control (DMAIC) model is developed and applied at a production line at a local company to identify and control root causes. Thorough analysis of collected data revealed that excess fluff, sap and pulp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
8
0
2
Order By: Relevance
“…LSS is a manufacturing strategy, which brings the process into control; eliminates waste hence enhancing the bottom-line results of any organization (Snee 2010 ). According to Mandahawi et al ( 2012 ), both Lean and Six Sigma are mutually compatible and the DMAIC approach becomes the core framework for process improvement and lean tools are embedded in each phase. But in today’s dynamic market low cost and quality are merely order qualifiers while product variety; customization and shorter lead-time have become order-winning criteria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…LSS is a manufacturing strategy, which brings the process into control; eliminates waste hence enhancing the bottom-line results of any organization (Snee 2010 ). According to Mandahawi et al ( 2012 ), both Lean and Six Sigma are mutually compatible and the DMAIC approach becomes the core framework for process improvement and lean tools are embedded in each phase. But in today’s dynamic market low cost and quality are merely order qualifiers while product variety; customization and shorter lead-time have become order-winning criteria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Singh and Khanduja (2012) employed Six Sigma in foundry operation and reduced the scrap for a two-wheeler’s piston castings by 15.02 percent. Mandahawi and Obeidat (2012) applied Six Sigma to minimize weight variation for Baby Lido Diaper manufacturing company and they decreased DMPO from 292,157 to 88,152 and improved the sigma level from 2.05 to 2.85. Hussain et al (2014) incorporated Sigma approach for reducing defects in textile weaving and improved sigma level from 2.2 to 3 and gained $26,000 profit per month.…”
Section: Classification Frameworkmentioning
confidence: 99%
“…The study proved that the DMAIC approach can be implemented without the expensive Six Sigma belt-based training. Mandahawi and Obeidat (2012) implemented a customized DMAIC approach to the production process of baby diapers and found that the significant variation causes were the fluff, sap and pulp excess. After the improvement phase, the defects per million opportunities (DPMO) were reduced from 292157 to 88152.…”
Section: Literature Reviewmentioning
confidence: 99%